The mischievous muse : extant poetry and prose by Ibn Quzman of Cordoba (d. AH 555/AD 1160) - Ibn Quzmān, Muḥammad ibn ʻAbd al-Malik, approximately 1080-1160. (Brill Studies in Middle Eastern Literatures, 2017)
The first part of this work includes all the known works of the twelfth-century Andalusi author Ibn Quzmān, most of which are zajal poems composed in the colloquial dialect of Andalus. They have been edited in a Romanized transliteration, and are accompanied by a facing-page English prose translation, along with notes and commentaries intended to elucidate matters relevant to each poem. In the second part of the work, sixteen chapters are devoted to analyzing specific poems from a literary perspective, in order to delve into their meaning and, thereby, explain the poet's literary goals.